A study on risk factors of hypertension among females residing in a rural block of West Bengal - Suman, Sweta; Paul, Bobby; Pan, Tania; Banerjee, Raharshi (International Journal Of Community Medicine And Public Health, 2018)
Background: A systematic review on the prevalence of HTN in India, for studies published between 1969 and July 2011, reported a range between 13.9 to 46.3% and 4.5 to 58.8% in urban and rural areas of India, respectively. Females are more negligent as far as health seeking behaviour is concerned. No study was found to report the status of risk factors of hypertension solely among the female population in this rural community of West Bengal. Thus, this study was undertaken with the purpose to highlight the status of known risk factors of hypertension among adults female population of a rural community of West Bengal. Methods: A community based cross-sectional study with systematic random sampling was conducted among 174 adult women residing in a rural area of West Bengal. Informed consent was obtained from the study participants. A structured questionnaire was used to collect data on various risk factors of hypertension. Analysis was done using SPSS (v 16). Results: Among 174 study participants, 54% were found to be hypertensive at the time of examination. Score according to number of risk factors was calculated and found to range from 2-10, the attainable score being 0-14. Median Systolic and diastolic Blood pressure was found to be more in group of individuals with more score. Conclusions: Modifiable risk factors were found to be present in considerable proportion of the study participants.